GENDER INSIGHT IN THE PROCESS OF HUMAN CREATION AL-QURAN PERSPECTIVE - K Khairuddin; P Perdamaian; S Suhaimi; Zaitun Abidin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This article examines the thoughts of a reforming Islamic figure who is a modern Muslim commentator and feminist figure regarding the origins of human creation, including what is contained therein, namely how the concept of gender has become a controversial topic among Islamic figures and Muslim feminists. Feminists claim that there is an element of discrimination against women in the interpretation of classical commentators where in every verse relating to gender, they seem to only elevate the status of men compared to women. However, in reality, Islam is not like that. Islam is a just religion, equalizing the status of men and women. With this discriminatory interpretation, feminists believe that it is necessary to reinterpret the verses of the Koran with a gender perspective, so that the concept of justice in Islam can be immediately revealed. The research method in this paper is a comparative method based on literature study. The results of this research will be able to reveal the concepts of nafs wahidah and zauj in surah al-Nisa verse 1 and al-Zumar (39): 6 which are key to the analysis of the gender problems faced.